Mostrare l’identità. Il ruolo sociale degli emblemi alle origini del processo di individualizzazione - Baglioni, Lorenzo Grifone (SocietàMutamentoPolitica, 2013)
The use of the emblems spreads within the cities of Europe in the first centuries after the Year 1000: the paper shows how this social phenomenon is related to the beginning of the individualization process. The signaletic and the symbolic practices related to the use of the emblems develop in parallel with the construction of the personal identity and the structuring of the social interdependence. With the emergence of both Court society and scientific sensitivity, the rapid araldic transformation of the emblems gives to the European ruling class the definitive monopoly of this extralinguistic code, erasing his early democratic meaning of personal autonomy expression.